Potato psyllids mount distinct gut responses against two different ‘Candidatus Liberibacter solanacearum’ haplotypes - Tang, Xiao-Tian; Levy, Julien; Tamborindeguy, Cecilia (PloS one, 2023)
‘ Candidatus Liberibacter solanacearum’ (Lso) is a bacterial pathogen infecting several crops and causing damaging diseases. Several Lso haplotypes have been identified. Among the seven haplotypes present in North America, LsoA and LsoB are transmitted by the potato psyllid, Bactericera cockerelli (Šulc), in a circulative and persistent manner. The gut, which is the first organ pathogen encounters, could be a barrier for Lso transmission. However, the molecular interactions between Lso and the psyllid vector at the gut interface remain largely unknown. In this study, we investigated the global transcriptional responses of the adult psyllid gut upon infection with two Lso haplotypes (LsoA and LsoB) using Illumina sequencing. The results showed that each haplotype triggers a unique transcriptional response, with most of the distinct genes elicited by the highly virulent LsoB. The differentially expressed genes were mainly associated with digestion and metabolism, stress response, immunity, detoxification as well as cell proliferation and epithelium renewal. Importantly, distinct immune pathways were triggered by LsoA and LsoB in the gut of the potato psyllid. The information in this study will provide an understanding of the molecular basis of the interactions between the potato psyllid gut and Lso, which may lead to the discovery of novel molecular targets for the control of these pathogens.